PENGARUH PENGGUNAAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA PADA PELAJARAN IPAS SEKOLAH DASAR KELAS - Arsurahmah, Aisyah; Hermita, Neni; Fendrik , Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low critical thinking skills of fifth-grade students at SD Negeri 105 Pekanbaru, particularly in Science and Social Studies (IPAS). This condition is caused by teacher-centered learning, making students passive in problem-solving. This study aimed to determine the effect of the Problem Based Learning (PBL) model on increasing students' critical thinking skills. This research involved 52 students divided into two groups: class VB as the experimental class (26 students) and class VD as the control class (26 students). The instrument used was a 20-item multiple-choice test focusing on three indicators: analyzing, evaluating, and concluding. The results showed a significant increase in the experimental class's average score from 49.42 (pretest) to 76.35 (posttest), while the control class only increased from 48.27 to 69.42. The Paired Sample t-test results showed a significance value (Sig. 2-tailed) of 0.000 < 0.05, meaning that the null hypothesis (Ho) was rejected. This is also supported by an N-Gain score of 0.508 (medium category) for the experimental class. Thus, it can be concluded that the PBL model has a significant influence on the critical thinking skills of fifth-grade students at SD Negeri 105 Pekanbaru.